Bahasa Inggris Bahasa Inggris: English - Rizky Prasetya (ELT in Focus, 2021)
Remote English teaching and learning must not be avoided at all costs during pandemic. Effective online instruction delivery is still a work in progress of Higher Education. The prior study explained that English pedagogy could have implemented in a virtual ecosystem. This study investigated learners’ viewpoints of online English for Specific purposes course in a higher education program. The mixed research design involving qualitative and quantitative approach provides detailed and accurate information about effective online English teaching. The instrument included aspects of effective online teaching. Data were collected through online questionnaire of 237 students’ responses towards online teaching. The twenty-one items identify elements that are described as very important to not important aspect of effective teaching, including socio-affective, subject-matter knowledge, pedagogical knowledge, and personality characteristics. The factors developed as participants include accommodating language learners’ needs, employing meaningful models, motivating language learners to do their most reliable, promoting the courses’ pattern entirely, giving a relevant course, interacting productively, and presenting adequate attention to learners. Online learners could learn as complete in face-to-face language classes. The online ecosystems’ view may motivate English lecturers to evaluate pedagogy in unconventional approach and designs. The study’s implication of online learning options has the possibility for language educational productivity, and it is also essential to recognise the pedagogical and practical advantages